Utilization of the School Library As a Learning Resource - Mastayufada, Nadhiva; Timan, Agus; Imron, Ali (Universitas Negeri Malang, 2024)
The management of special services in schools is essential to support the learning process. These services include counseling, libraries, health units and various other facilities, all aimed at meeting the special needs of students. The library, as an information center, plays a crucial role in providing learning resources and supporting academic activities. Despite this, many students do not utilize the library optimally due to various obstacles, such as lack of awareness of its importance and easy access to technology. Therefore, the library should function not only as a place to store books, but also as an effective learning tool. Good management includes planning, organizing, mobilizing and monitoring. Through these strategies, the library can attract students' interest, improve literacy skills and create a conducive learning environment. Thus, the library contributes significantly to the success of education in schools.